Cyclooxygenase‐2 and 5‐Lipoxygenase in Dogs with Chronic Enteropathies. (30th September 2014) - Dumusc, S.D.; Ontsouka, E.C.; Schnyder, M.; Hartnack, S.; Albrecht, C.; Bruckmaier, R.M.; Burgener, I.A.
<x xml:space="preserve">Abstract</x> Background Cyclooxygenase‐2 (COX‐2) is a key enzyme in the synthesis of pro‐inflammatory prostaglandins and 5‐lipoxygenase (5‐LO) is the major source of leukotrienes. Their role in IBD has been demonstrated in humans and animal models, but not in dogs with chronic enteropathies (CCE). Hypothesis COX‐2 and 5‐LO are upregulated in dogs with CCE. Animals Fifteen healthy control dogs (HCD), 10 dogs with inflammatory bowel disease (IBD), and 15 dogs with food‐responsive diarrhea (FRD). Methods Prospective study. mRNA expression of COX‐2, 5‐LO, IL‐1b, IL‐4, IL‐6, TNF, IL‐10 and TFG‐β was evaluated by quantitative real‐time RT‐PCR in duodenal and colonic biopsies before and after treatment. Results COX‐2 expression in the colon was significantly higher in IBD and FRD before and after treatment (all P < .01). IL‐1b was higher in FRD in the duodenum after treatment (P = .021). TGF‐β expression was significantly higher in the duodenum of HCD compared to FRD/IBD before treatment (both P < .001) and IBD after treatment (P = .012). There were no significant differences among groups and within groups before and after treatment for IL‐4, IL‐6, TNF, and IL‐10. There was a significant correlation between COX‐2 and IL‐1b in duodenum and colon before treatment in FRD and IBD, whereas 5‐LO correlated better with IL‐6 and TNF. IL‐10 and TGF‐β usually were correlated. Conclusions and Clinical Importance COX‐2 is upregulated in IBD and FRD, whereas IL‐1b and TGF‐β seem to be important pro‐ and anti‐inflammatory cytokines, respectively. The use of dual COX/5‐LO inhibitors could be an interesting alternative in the treatment of CCE.